School Leaders' Perspectives on Successful Leadership: A Mixed Methods Case Study of a Private School Network in Pakistan - Raza, Mehwish; Gilani, Nadia; Waheed, Syed Abdul (Frontiers in Education, 2021)
Private school culture dominates the public-school culture in Pakistan. With no central regulating organization, private schools in the country autonomously construct their educational philosophy that underpins curriculum choice, pedagogic approaches, and school operations. In this perspective, there is an increasing inquisitiveness in the understanding of what determines a private school as a “successful” school. The researchers intend to understand the determinants of a successful private school and aim to explore the leadership behaviors of head teachers of such schools in Pakistan. The Beaconhouse School System (BSS), the largest private school system in Pakistan, took part in this case study. A sample of a total of 128 participants, comprising of teachers (n = 120), School Group Heads (SGH) (n = 4) and school head teachers (n = 4) of four most successful primary schools of BSS, was drawn to participate in this case study employing a mixed-methods design. Two survey instruments, Determinants of School Success (DSS) and Leadership Practice Index (LPI) were developed on a five-point Likert Scale and applied to identify four most successful primary schools of BSS. It was found that head teachers had established a whole-school approach towards students high achievement, promoted a culture of trust, commitment, shared vision, practiced distributed leadership and involved all stakeholders in creating a shared sense of direction for the school. Recommendations have been generated for improving the performance of school leaders.